PEDAGOGICAL DIAGNOSTICS IN THE CONTEXT OF PEDAGOGY - Adash Rustamova Eshankulovna; Qayumova Shaxnoza Anvar qizi (Scholar Express Journals, 2023)
This article discusses the importance of pedagogical diagnostics Pedagogical diagnostics plays an important role in the analysis of the effectiveness of education, the content of work, the pedagogical activity carried out, this method of work is successfully implemented in advanced educational institutions, the achievements are strengthened, the analysis of shortcomings and deficiencies on the basis of which the main strategic directions are determined and high-level final results are achieved.
Keywords: pedagogical diagnostics; philological; practical conclusions